Principles of Visual Anthropology. - Hockings, Paul (de Gruyter Mouton, 2012)
This edition contains 27 articles, written by scholars and film makers who are generally acknowledged as the international authorities in the filed. The book covers ethnographic filming and its relations to the cinema and television; applications of filming to anthropological research, the uses of still photography, archives, and videotape; subdisciplinary applications in ethnography, archeology, bio-anthropology, museology and ethnohistory; and overcoming the funding problems of film production.